Pengembangan Sistem Informasi Sekolah Berbasis Web Dua Bahasa SMA Muhammadiyah Gading Rejo - Lulud Oktaviani; Mutiara Ayu (Universitas Mathla'ul Anwar Banten, 2021)
DEVELOPING BILINGUAL WEB-BASED SCHOOL INFORMATION SYSTEM AT SMA MUHAMMADIYAH GADING REJO. This study aimed at developing a bilingual web-based school information system as a medium to promote and deliver school information to students, parents and community. This system is equipped with school profile information, school facilities, school achievement and documentation that can provide an overview of the school. As a result, parents can select the best school for their children in accordance with their talents and interests. The research method used is a research and development through preliminary research, design and realization. The system is developed by using PHP language and MySQL. All components of the application, which include the user interface, processing scripts and database reside on the server. The website is http://smamuhammadiyahgadingrejo.com.